Existing competitive indices in the intercropping system of Manihot esculenta Crantz and Lagenaria siceraria (Molina) Standley. Issue 1 (1st January 2016) - Doubi, Bi Tra S.; Kouassi, Kouadio I.; Kouakou, Kouakou L.; Koffi, Kouamé K.; Baudoin, Jean-Pierre; Zoro, Bi Irié A.
ABSTRACT: An assessment of the competitive indices in intercropping between cassava ( Manihot esculenta ) and bottle gourd ( Lagenaria siceraria ) was conducted with the aim of increasing the productivity of these crops. For this purpose, three farmers preferred landraces of cassava ( yacé, blêbou and six mois ) and three morphotypes of gourd (dark green and round fruit, light green and round fruit, light green and long fruit) were used to test the three intercropping ratios (gourd:cassava with 6:42, 6:24 and 6:18). Intercropping systems were assessed by land equivalent ratio (LER), area time equivalent ratio (ATER), relative crowding coefficient ( K ), actual yield loss (AYL), aggressivity ( A ) and competition ratio (CR). LER, ATER and K values were greater than 1 for gourd-cassava (6:24). These findings indicate an advantage of intercropping for exploiting the resources of the environment. Cassava clones were more competitive than gourd component.